Application of the FDTD Method for Multivariate Analysis of the Influence of Conductivity and the Arrangement of Hollows Inside Bricks on the Values of Electric Field Intensity - Agnieszka Choroszucho; Tomasz Szczegielniak; Dariusz Kusiak (Energies, 2024)
The article contains a numerical analysis of the effects of electromagnetic wave propagation in an area containing a non-ideal, non-uniform, and absorbing dielectric. The analysis concerned the influence of the structure of the building material and its electrical parameters on the electric field intensity. The analysis took into account the variability of the number of hollows in the brick, the width of hollows, as well as the arrangement of these hollows relative to each other using the example of two types of bricks. The article also provides the most commonly used values of electrical parameters for building materials (brick, plaster). For this reason, the article includes results for different values of conductivity (0–0.2 S/m). The FDTD (Finite Difference Time Domain) method was used for multivariate analysis. The aim was to verify the correctness of the numerical assumptions adopted. Using the example of the most commonly used wall structure in construction, the results obtained using the FDTD method were compared with values obtained using another numerical method, the finite element method (FEM). The influence of an additional layer of plaster on the considered wall on the electric field was also checked. The analysis showed that a symmetrical arrangement of bricks results in higher values of the electric field by an average of 20%. Of course, this depends on the length of the hollows and the number of holes. The highest field values occur at low conductivities (0–0.04 S/m). A brick wall with a larger number of hollows and a symmetrical brick arrangement shows the highest electric field intensity, especially for hollow sizes (0.009–0.015 m).